Synchronously enhanced biofilm formation and m-dichlorobenzene removal in biotrickling filters by rhamnolipid chelating rare earth elements. Issue 1 (31st December 2022) - Yang, Bairen; Wang, Jiajie; Shang, Qingqing; Sun, Zhuqiu; Wu, Yifan
ABSTRACT: The effects of rhamnolipid chelating La (III) or Nd (III) on m -dichlorobenzene removal and biofilm growth were investigated. The rhamnolipid chelating La (III) or Nd (III) significantly increased the average m -dichlorobenzene elimination capacity by 24% and 29%, respectively, on day 70–130, and the average wet weights of biomass ranged from 11 kg/m 3 to 15 kg/m 3 in BTFs on day 100–180 at an inlet load of at 47–98 gm 3 /h and an EBRT of 60s-90s. Microbial community functional genes about biofilm growth and m -dichlorobenzene removal were also increased. In addition, the rhamnolipid chelating La (III) or Nd (III) can improve the membrane permeability, extracellular polymeric substance (EPS) production, catechol 2, 3 dioxygenase (C23O) enzyme, and chlorobenzene dioxygenase activity. These results demonstrate that rhamnolipid chelating La (III) or Nd (III) have the potential to improve the performance of BTFs treating hydrophobic and highly toxic VOCs. Graphical Abstract: uf0001